New Microbial Technologies for Advanced Biofuels 2015
DOI: 10.1201/b18525-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structures Differentiated in a Single-Chamber Air-Cathode Microbial Fuel Cell Fueled with Rice Straw Hydrolysate

Abstract: Background: The microbial fuel cell represents a novel technology to simultaneously generate electric power and treat wastewater. Both pure organic matter and real wastewater can be used as fuel to generate electric power and the substrate type can influence the microbial community structure. In the present study, rice straw, an important feedstock source in the world, was used as fuel after pretreatment with diluted acid method for a microbial fuel cell to obtain electric power. Moreover, the microbial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Previous study showed that it was possible to generate electricity from hydrolysate of cellulosic biomass, such as steam-exploded cornstalk (Zuo et al, 2006), wheat straw (Zhang et al, 2009) and rice straw (Wang et al, 2014b). All these reports were performed in batch mode focused on either feasibility of electricity generation or the analysis of microbial diversity.…”
Section: Degradation Efficiency Of Cornstalk Hydrolysatementioning
confidence: 99%
See 2 more Smart Citations
“…Previous study showed that it was possible to generate electricity from hydrolysate of cellulosic biomass, such as steam-exploded cornstalk (Zuo et al, 2006), wheat straw (Zhang et al, 2009) and rice straw (Wang et al, 2014b). All these reports were performed in batch mode focused on either feasibility of electricity generation or the analysis of microbial diversity.…”
Section: Degradation Efficiency Of Cornstalk Hydrolysatementioning
confidence: 99%
“…Distinguished from previous study (Wang et al, 2014a,b;Zhang et al, 2009), Proteobacteria which a number of exoelectrogens belong to, was not dominant on the electrode surface of FBMFC in this study. One possible reason is the different niches with diverse environment existing in MFC fed with lignocellulose hydrolysate (Wang et al, 2014b), including degradation of macromolecules (i.e. cellulose and lignin) and conversion of small molecules (i.e.…”
Section: Characterization Of Microbial Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The products were further purified using the QIAquick PCR purification kit (Qiagen) [22]. In order to reduce the bias from replicates and recover sufficient amount of purified amplicons, PCR products from replicates were combined before purification steps [39]. Pyrosequencing of the amplicons was performed by Macrogen (Seoul, South Korea) using a 454/Roche GS-FLX titanium instrument (Roche, NJ).…”
Section: Dna Extraction Pcr Amplification and 454 Titanium Pyrosequmentioning
confidence: 99%
“…The consortium mainly consisted of Bacteroidetes (40%), Alphaproteobacteria (20%), Bacillus (20%), Deltaproteobacteria (10%), and Gammaproteobacteria (10%), while the suspended consortia were predominately Bacillus (22.2%). The microbial community composition may change after MFC operation depending on niches, sulfate-reducing bacteria accounted for large relative abundance [79].…”
Section: Microorganism Substrate Fuels and Operation Conditionsmentioning
confidence: 99%